Excess of leptin inhibits hypothalamic expression in pubertal mice - Sung Yeon Ahn; Sei Won Yang; Hee Jae Lee; Jong Seon Byun; Ji Yeon Om; Choong Ho Shin (Korean Pediatric Society, 2012)
PurposeLeptin has been considered a link between metabolic state and reproductive activity. Defective reproductive function can occur in leptin-deficient and leptin-excessive conditions. The aim of this study was to examine the effects of centrally injected leptin on the hypothalamic KiSS-1 system in relation to gonadotropin-releasing hormone (GnRH) action in the initial stage of puberty.MethodsLeptin (1 µg) was injected directly into the ventricle of pubertal female mice. The resultant gene expressions of hypothalamic GnRH and KiSS-1 and pituitary LH, 2 and 4 hours after injection, were compared with those of saline-injected control mice. The changes in the gene expressions after blocking the GnRH action were also analyzed.ResultsThe basal expression levels of KiSS-1, GnRH, and LH were significantly higher in the pubertal mice than in the prepubertal mice. The 1-µg leptin dose significantly decreased the mRNA expression levels of KiSS-1, GnRH, and LH in the pubertal mice. A GnRH antagonist significantly increased the KiSS-1 and GnRH mRNA expression levels, and the additional leptin injection decreased the gene expression levels compared with those in the control group.ConclusionThe excess leptin might have suppressed the central reproductive axis in the pubertal mice by inhibiting the KiSS-1 expression, and this mechanism is independent of the GnRH-LH-estradiol feedback loop.